The Ilioinguinal Surgical Approach Using a Modified Medial Window: Origin, Evolution, and Applications. A 34-Year Perspective. (February 2019) - Mayo, Keith; Unno, Florence
Abstract : Summary: Emile Letournel's ilioinguinal approach provided unprecedented surgical access to the anterior aspect of the innominate bone. A refinement of this approach is described which incorporates a modified medial window that limits dissection around the external iliac vessels, expands surgical exposure of the anterior pelvic ring, and provides additional reduction possibilities while preserving the capabilities of the lateral and middle windows. Abstract : Supplemental Digital Content is Available in the Text.